Effects of atrial natriuretic polypeptide on rat hypothalamic neurones in vitro. - Okuya, S (1987)
1. Extracellular recordings were made from 175 spontaneously active cells in the rat coronal hypothalamic slice preparation. Reconstruction of the recording sites showed that fifteen were in the supraoptic nucleus (s.o.n.), ten in the magnocellular portion of the paraventricular nucleus (p.v.n.) which could be antidromically activated by stimulation lateral to the nucleus, seventy-seven other cells in the p.v.n. and seventy-three in the anteroventral third ventricle (a.v.3.v.) region. 2. The mean firing rates (mean +/- S.E. of mean) of the spontaneously firing cells in the s.o.n., p.v.n. and a.v.3.v. were 2.8 +/- 0.4 spikes/s, 2.9 +/- 0.2 spikes/s and 5.0 +/- 0.4 spikes/s, respectively. Antidromically identified p.v.n. cells fired spontaneously with a mean firing rate of 1.5 +/- 0.5 spikes/s. 3. Bath application of atrial natriuretic polypeptide (a.n.p.; 10(-7) M) had no effect on fifteen s.o.n. cells tested but nineteen (22%) of eighty-seven p.v.n. cells (including two of the ten antidromically activated cells) and thirty (41%) of seventy-three a.v.3.v. cells showed inhibitory responses. Three (3%) cells in the p.v.n. were excited by a.n.p. 4. The dose dependence of the response to a.n.p. was tested in two p.v.n. and five a.v.3.v. cells. As a.n.p. concentration increased, the firing rates of all seven cells generally decreased. However, one a.v.3.v. neurone was excited at low concentrations (less than 10(-8) M) but inhibited at high concentrations (10(-7) and 10(-6) M) of a.n.p. The threshold concentration to evoke inhibitory responses in the p.v.n. was 10(-10) M and in the a.v.3.v. was 10(-11) M. 5. With the exception of the two antidromically activated p.v.n. cells, the inhibitory effect of a.n.p. still persisted after synaptic transmission had been suppressed with a low-Ca2+ and high-Mg2+ medium. 6. Thirty-six cells in the a.v.3.v. were tested with both a.n.p. and angiotensin II applied at 10(-7) M. Twelve showed inhibitory responses to a.n.p. and nine showed excitatory responses to angiotensin II. In other experiments, a.n.p., angiotensin II and arginine-vasopressin were each applied to neurones in the p.v.n. Of the forty cells tested with all three peptides at 10(-7) M, seven were inhibited by a.n.p., fourteen were excited by angiotensin II and twenty were excited by arginine-vasopressin. No neurones in either the p.v.n. or a.v.3.v. were inhibited by a.n.p. and excited by angiotensin II, but four neurones in the p.v.n. were inhibited by a.n.p. and excited by arginine-vasopressin.(ABSTRACT TRUNCATED AT 400 WORDS)